Small-Conductance Ca2+-Activated K+ Channels 2 in the Hypothalamic Paraventricular Nucleus Precipitates Visceral Hypersensitivity Induced by Neonatal Colorectal Distension in Rats - Ji, Ning-Ning; Du, Lei; Wang, Ying; Wu, Ke; Chen, Zi-Yang; Hua, Rong; Zhang, Yong-Mei (Frontiers in Pharmacology, 2021)
Visceral hypersensitivity is one of the pivotal pathophysiological features of visceral pain in irritable bowel syndrome (IBS). Small-conductance Ca2+-activated K+ channel (SK) is critical for a variety of functions in the CNS, whether it is involved in the pathogenesis of visceral hypersensitivity remain elusive. In this study, we examined mechanism of SK2 in hypothalamic paraventricular nucleus (PVN) in the pathogenesis of visceral hypersensitivity induced by neonatal colorectal distension (CRD). Rats undergoing neonatal CRD presented with visceral hypersensitivity as well as a downregulation of membrane SK2 channel and p-PKA. Intra-PVN administration of the membrane protein transport inhibitor dynasore increased the expression of membrane SK2 in PVN and alleviated visceral hypersensitivity, as well as PVN administration of the SK2 activator 1-EBIO. In addition, 1-EBIO reversed the increase in neuronal firing rates in PVN in rats undergoing neonatal CRD. On the contrary, intra-PVN administration of the SK2 inhibitor apamin aggravated the visceral hypersensitivity, and the same was also true of the intra-PVN administration of PKA activator 8-Br-cAMP. Taken together, these results demonstrate that visceral hypersensitivity is related to the decrease of membrane SK2 in PVN, which may be regulated by the activation of PKA; pharmacologic activator of SK2 alleviated visceral hypersensitivity, suggesting SK2 activators as a new intervention for visceral pain.